2003
DOI: 10.1093/bja/90.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of measured and estimated angles of table tilt at Caesarean section

Abstract: Estimation of the angle of table tilt is unreliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 3 publications
1
11
0
1
Order By: Relevance
“…They were then asked to estimate the degree of tilt they had applied and the actual tilt was measured using the iHandy Level© iPhone app. As in a prior study , my study reiterated that the perceived tilt applied to the operating tilt was grossly overestimated. Interestingly, in our study the degree of overestimation was greatest amongst obstetricians compared with anaesthetists, with a median (IQR) error of 14° (10°–25°) compared with 12° (5°–22°), respectively.…”
supporting
confidence: 56%
“…They were then asked to estimate the degree of tilt they had applied and the actual tilt was measured using the iHandy Level© iPhone app. As in a prior study , my study reiterated that the perceived tilt applied to the operating tilt was grossly overestimated. Interestingly, in our study the degree of overestimation was greatest amongst obstetricians compared with anaesthetists, with a median (IQR) error of 14° (10°–25°) compared with 12° (5°–22°), respectively.…”
supporting
confidence: 56%
“…We used two wedges that were designed for this purpose to ensure accurate angle estimation. It had been previously reported that over-estimation of tilting angle is common among obstetric anesthetists [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once the woman is positioned supine for surgery, left uterine displacement is routinely used to reduce inferior vena cava compression, with a recommended angle of 15° . This angle of table tilt is associated with higher maternal SAP and cardiac output and lower doses of infused phenylephrine than the unmodified supine position , but is seldom achieved in practice . If the table is tilted to 15°, lateral support is required for security.…”
Section: Cardiovascular Changes After Spinal Anaesthesiamentioning
confidence: 99%